MODERN APPROACHES IN LANGUAGE EDUCATION - Avezova Dilnura Bayramovna (Galaxy International Interdisciplinary Research Journal, 2024)
The article focuses on the teaching of the mother tongue in general secondary educational institutions, modern approaches and their advantages in increasing the effectiveness of education, as well as on the development of students’ speech and the formation of correct pronunciation skills. methodical assignments are also included.